Tribological performance of c-alloyed WS 2 coatings with graded and conventional structures - Leviandhika, Vidhiaza Muhammad (2021)
Dissertação de Mestrado Conjunto Europeu em Tribologia de Superficies e Interfaces apresentada à Faculdade de Ciências e Tecnologia